â The most common causes of project failure lie in the project environment â. Discuss the extent to which you agree with this statement - Whittingham, Neil (Nalars, 2010)
In recent decades the interest in the academic study of projects and their management has grown considerably. Theorists have conceptualised peopleâs endeavours in order to provide a clearer understanding of processes, systems and relationships involved. Research into scoping, design, implementation and the outcomes and values of products and services, once a project is considered complete or has terminated, can provide insights to help inform the better management of projects in the future, through grasping what have been key factors in the success or failure of particular projects. Examples in the academic, project management literature can range from the consideration of projects in the slums of a developing country to organising a flight to another planet ( Viratkapan and Prerera, 2006; Sauser et al, 2009 ). The evolving field of study aims for both the development of general concepts that can be applied to many walks of life, and also insights that relate to particular types of circumstances. Sauser (2009) considers that the evolving research of project management has been more focussed on success factors rather than analysis of failure and potential solutions. Despite this, to reflect on whether the most common causes of project failure lie in the project environment, this essay is in three basic sections. Firstly, an outline is given of how project failure and the project environment can be conceived. Secondly, there is a review of discoveries from the governmental and academic literature that aims to point out the reasons for project failure. This is followed by a critical reflection on the literature, and consideration of who judges the quality of project outcomes and how they do it, to bring the essay to a conclusion.